1978
DOI: 10.1137/1122049
|View full text |Cite
|
Sign up to set email alerts
|

On the Strong Mixing Property for Linear Sequences

Abstract: Let Zi, =0, +/-1, +/-2,..., be a sequence of independent random variables with characteristic functions (c.f.) rpi(u) and probability densities pi(x), and let {gk}, k O, 1, 2, ", be a certain sequence of numbers: go 0. Suppose that there exist random variables X for which XIN =o giZj-i-X converges weakly to zero as N 00 and Ixl < a.s. Chanda [1] formulated the following result: if Z are identically distributed, ElZol < , g0=l, Io(u)ldu<=l and then X/ satisfy the strong mixing (s.m.) condition with mixing coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(58 citation statements)
references
References 4 publications
1
57
0
Order By: Relevance
“…In…nite order distributed lags, for example, need not be mixing due to density smoothness requirements, including ARFIMA, nonlinear ARMA-GARCH and some long memory processes. See Gorodetskii (1977), Andrews (1984), Guegan and Ladoucette (2001), Carrasco and Chen (2002) and Wu (2005).…”
mentioning
confidence: 99%
“…In…nite order distributed lags, for example, need not be mixing due to density smoothness requirements, including ARFIMA, nonlinear ARMA-GARCH and some long memory processes. See Gorodetskii (1977), Andrews (1984), Guegan and Ladoucette (2001), Carrasco and Chen (2002) and Wu (2005).…”
mentioning
confidence: 99%
“…For example, Chanda (1974) first presented that linear stochastic process is strong mixing. Gorodeskii (1977) showed that linear process is strong mixing under certain conditions and also provided the convergent rate for the strong mixing coefficient. Withers (1981) further gave an alternative set of conditions for linear processes to be strong mixing, and proved the strong mixing coefficient is polynomial decay under some conditions.…”
Section: Introductionmentioning
confidence: 95%
“…Assumption 1 includes a wide variety of possible data-generating mechanisms. For example, both the ARMA process and the MA(∞) process can become strongly mixing under some regularity conditions (see, e.g., Gorodetskii [1977] and Withers [1981]). The mixing condition in this assumption essentially controls the extent of permissible temporal dependence in the process in the relation to the probability of outlier occurrences.…”
Section: A(l)x Tmentioning
confidence: 99%